Recent progress in genome engineering techniques in the silkworm, Bombyx mori. (1st November 2013) - Daimon, Takaaki; Kiuchi, Takashi; Takasu, Yoko
<x xml:space="preserve">Abstract</x> Rapid advances in genome engineering tools, such as zinc finger nucleases (ZFNs), transcription activator‐like effector nucleases (TALENs), and the clustered regularly interspaced palindromic repeats/CRISPR‐associated (CRISPR/Cas) system, have enabled efficient gene knockout experiments in a wide variety of organisms. Here, we review the recent progress in targeted gene disruption techniques in the silkworm, Bombyx mori. Although efficiency of targeted mutagenesis was very low in an early experiment using ZFNs, recent studies have shown that TALENs can induce highly efficient mutagenesis of desired target genes in Bombyx. Notably, mutation frequencies induced by TALENs can reach more than 50% of G0 gametes. Thus, TALENs can now be used as a standard tool for gene targeting studies, even when mutant phenotypes are unknown. We also propose guidelines for experimental design and strategy for knockout experiments in Bombyx. Genome editing technologies will greatly increase the usefulness of Bombyx as a model for lepidopteran insects, the major agricultural pests, and lead to sophisticated breeding of Bombyx for use in sericulture and biotechnology.